2021
DOI: 10.1029/2020jd033860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Forecast Performance for Extreme Cold Events in East Asia With Subseasonal‐to‐Seasonal Data Sets From ECMWF

Abstract: is often subjected to the influence of extreme cold events during the boreal winter. Observations show that the frequency of winter extreme cold events has increased during the past two decades and East Asia has experienced several severe extreme cold events in the past few winters (Cohen et al., 2020; Johnson et al., 2018). For example, an unprecedented low-temperature and freezing disaster occurred in southern China in early January 2008, which caused hundreds of human deaths and great economic loss (Ding et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Forecasts and reforecasts are initialized twice a week. Previous evaluations of ECMWF indicate good performance up to lead times of 7-10 days for extreme cold events 93 , up to 11 days for daily precipitation 94 , up to 15 days for heatwaves 95,96 , and up to 20 days for soil moisture 97 .…”
Section: Subseasonal Forecastsmentioning
confidence: 96%
“…Forecasts and reforecasts are initialized twice a week. Previous evaluations of ECMWF indicate good performance up to lead times of 7-10 days for extreme cold events 93 , up to 11 days for daily precipitation 94 , up to 15 days for heatwaves 95,96 , and up to 20 days for soil moisture 97 .…”
Section: Subseasonal Forecastsmentioning
confidence: 96%
“…Dai, Mu, Li et al. (2021) proposed that certain long and persistent extreme cold events may exhibit a skillful forecast lead time longer than 2 weeks. Besides, Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, Buizza and Leutbecher (2015) pointed out that forecast skills longer than 2 weeks are achievable owing to major advances in data assimilation, modeling and ensemble techniques. Dai, Mu, Li et al (2021) proposed that certain long and persistent extreme cold events may exhibit a skillful forecast lead time longer than 2 weeks. Besides, Liu et al (2016) indicated that boundary conditions are important for the forecast at extended-range timescales.…”
mentioning
confidence: 99%
“…Previous research suggests that long‐lasting phenomena may have a long predictability that can reach four pentads or even beyond (Buizza & Leutbecher, 2015; Dai et al., 2021; Vitart & Robertson, 2018). Dai et al.…”
Section: Introductionmentioning
confidence: 99%
“…minus one standard deviation was about 12 days (Dai et al, 2021). In the winter of 2020/2021, three successive cold surges adversely affected East Asia, in which the daily mean temperature in many regions of China, Korea and Japan dropped below the 10th percentile of the period 1979-2019 (Dai et al, 2022;X.…”
mentioning
confidence: 99%